1976
DOI: 10.1099/00221287-96-2-401
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogen Peroxide on Spores of Clostridium bifermentans

Abstract: The effect of hydrogen peroxide on the germination, colony formation and structure of spores of Clostridium bifermentans was examined. Treatment with 0.35 M-hydrogen peroxide increased the germination rate at 25 "C but increasing the temperature or concentration of hydrogen peroxide decreased both the germination rate and colony formation. The presence of Cu2+ increased the lethal effect of hydrogen peroxide on colony formation as much as 3000-fold. Preincubation of spores with Cu2+ before treatment with hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 17 publications
(7 reference statements)
2
32
0
Order By: Relevance
“…We have shown previously that addition of 10 ,LAM-CU~+ caused a fivefold increase in the lethal effect of H202 on spores of Clostridium bifermentans and that addition of other divalent metal ions also slightly increased the kill (Bayliss & Waites, 1976). Preliminary results suggested that such ions do not markedly increase the effect of H20, on spores of other species.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…We have shown previously that addition of 10 ,LAM-CU~+ caused a fivefold increase in the lethal effect of H202 on spores of Clostridium bifermentans and that addition of other divalent metal ions also slightly increased the kill (Bayliss & Waites, 1976). Preliminary results suggested that such ions do not markedly increase the effect of H20, on spores of other species.…”
Section: Introductionmentioning
confidence: 56%
“…7b). We have shown that the resistance of spores of C. bifermentans to H20, was only slightly decreased by the presence of Fe2+ (Bayliss & Waites, 1976). It is probable, therefore, that only those metal ions like Cu2+ which bind to protoplasts are able to decrease spore resistance.…”
Section: Efect Of Metal Ions On Germination With Lysozyme Of Sporesmentioning
confidence: 85%
See 3 more Smart Citations